Suku Phyllanthaceae pada Rawa Bakau dan Tambak di Telang Asri, Kabupaten Bangkalan, Pulau Madura: Phyllanthaceae of Mangrove Swamp and Fishpond in Telang Asri, Bangkalan Regency, Madura Island - Irsyam, Arifin Surya Dwipa; Muhammad Rifqi Hariri; Irwanto, Rina Ratnasih; Setiawan, Ashari Bagus (Jurnal Sumberdaya Hayati, 2020)
Madura island is known as a mixed deciduous forest area with dry seasons and limestone soil. The island has unique plant species compared to the mainland Java. However, most of the mangrove forest areas have been converted into ponds and housing. One of the remaining mangrove swamps is located at Telang Asri village, Kamal Subdistrict, Bangkalan Regency. Several species of mangroves have been reported here, along with other groups of plants from the Phyllanthaceae family, found numerously at the time of observation. In 1963, CA Backer and RC Bakhuizen van den Brink Jr. have already listed 16 species of Phyllanthaceae from Madura Island. Since then, the updated information on the Phyllanthaceae of Madura has not been available. Therefore, this study aimed to collect the members of Phyllanthaceae family in the mangrove swamp areas of Telang Asri village. The field study was carried out using the exploratory method, while specimen preparation was conducted in Herbarium Bandungense (FIPIA). In this study, seven species were collected from Telang Asri, namely Glochidion littorale Blume, G. zeylanicum (Gaertn.) A. Juss., Phyllanthus amarus Schumach. and Thonn., P. debilis Klein ex Willd., P. reticulatus Poir., P. urinaria L., and P. virgatus G. Forst.